Penerapan Model Problem Based Learning Berbantuan Puzzle untuk Meningkatkan Hasil Belajar Siswa tentang Pengamalan Nilai-Nilai Pancasila dalam Kehidupan Sehari-Hari di Kelas VI UPTD SD Inpres Oesapa Kecil 1 - Ditte, Angela Petronela; Kota, Martha Khistina; Ga, Paulina Riwu (Lembaga Yasin AlSys, 2025)
This study aims to improve student learning outcomes in the subject of Pancasila Education, specifically related to the practice of Pancasila values in daily life, through the implementation of the Problem Based Learning (PBL) model assisted by puzzle media. This research employs Classroom Action Research (CAR), carried out in four stages: planning, implementation, observation, and reflection. The research subjects were 25 sixth-grade students of Class VI C at UPTD SD Inpres Oesapa Kecil 1. Data were collected through observation and tests, then analyzed through data reduction, data presentation, and conclusion drawing. The results show a significant increase in students’ average scores, from 56.92 in the pre-cycle to 72.06 in Cycle I, and further to 84.63 in Cycle II. The percentage of students achieving mastery learning also increased from 36% in the pre-cycle, to 44% in Cycle I, and reached 100% in Cycle II. These findings indicate that the application of the PBL model assisted by puzzle media is effective in enhancing student learning outcomes. In addition to improving conceptual understanding, this approach promotes more active and meaningful learning, while also fostering students’ motivation and participation in understanding and practicing Pancasila values.